Information Behavior Analysis of Lampung University Students: Searching Process for Scientific Paper and Circulation Collection: a Case Study - Erni Fitriani, Sugiyanta - (Palimpsest: Jurnal Ilmu Informasi dan Perpustakaan, 2021)
Information and communication technology in its development has an effect on human life covering social, economic, cultural aspects, including libraries.Libraries are required to provide up to date information and in diverse forms. There are differences in information behavior of University Students of Lampung on searching collections of scientific paper and circulation collections. The aims of this research are  to find out the information behavior of students of Lampung University in the process of tracing collections of scientific works and circulation collections, and mention the similarities and regulations of information behavior in the search of collections of scientific works and searches of circulation collections. This research methode uses qualitative descriptive with data collection techniques through observation, documentation data and literature study. The results obtained  are :  information behavior University Student of Lampung on searching collections of scientific papers are: most students of Lampung University on searching collection of scientific papers using a laptop to access on the link: digilib.unila.ac.id., log in, search the faculty, study programs, published years and titles of scientific paper, do the citation, and save cited to file work. Information behavior University Students of Lampung on searching   circulation collections are: most University Student of Lampung on searching circulation collections using the computer library provided, access on the link: opac.unila.ac.id (online catalog), write down the name of the author or the title of book, record the call number of the circulation collections of interest, to the circulation collection shelves, take circulation collections to read or borrow to take home. But there are also similarities in the behavior of information in the process of disseminating the collection of scientific works and tracing the circulation collection, namely both the search process is done online and search for information by writing the title of the work both books and scientific works.Keywords: information behavior, University Student of Lampung, scientific paper                   collections, circulation collections, University Library of Lampung